7x-3 - 9-4x = 7-x                                                                                                                                              ------ - ------=------                              решите уравнение...

7x-3 - 9-4x = 7-x                                                                                                                                              ------ - ------=------                              решите уравнение                                                                                                   2            3         2
Гость
Ответ(ы) на вопрос:
Гость
(7х-3)/2-(9-4х)/3=(7-х)/2, избавимся от дроби, все уравнение умножим на 6 3(7х-3)-2(9-4х)=3(7-х) 21х-9-18+8х=21-3х 32х=48 х=48/32=1 целая 1/2=1,5
Гость
7x-3-9-4x=7-x 7x-4x+x=3+9+7 4x=19 x=4,75
Не нашли ответ?
Ответить на вопрос
Похожие вопросы